2018
DOI: 10.1073/pnas.1810060115
|View full text |Cite
|
Sign up to set email alerts
|

Switchable control over in vivo CAR T expansion, B cell depletion, and induction of memory

Abstract: SignificanceChimeric antigen receptor (CAR) T cell therapy represents a powerful strategy in immuno-oncology. Nevertheless, associated life-threatening toxicities and chronic B cell aplasia have underscored the need to control engineered T cells in the patient. To address these challenges, we have previously developed a switchable CAR (sCAR) T cell platform that allows dose-titratable control over CAR T cell activity by using antibody-based switches. Here, we demonstrate in a syngeneic murine model that the sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 52 publications
(81 reference statements)
4
62
0
Order By: Relevance
“…Furthermore, this persistence was associated with elevated expression of exhaustion markers such as PD1 and LAG3, similar to the antigen‐dependent persistence described in models of chronic viral infection . This hypothesis is further supported by preclinical data in which CAR T cell recognition of CD19 was dependent upon a soluble “switch” molecule, which allowed for the temporal control of CAR T cell activation . Using this model, the authors demonstrated enhanced CAR T cell persistence and re‐expansion when the CAR T cells experience antigen activation in a pulsatile manner as opposed to continuous activation by endogenous CD19 .…”
Section: Antigen Positive Escape and Car T Cell Persistencesupporting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, this persistence was associated with elevated expression of exhaustion markers such as PD1 and LAG3, similar to the antigen‐dependent persistence described in models of chronic viral infection . This hypothesis is further supported by preclinical data in which CAR T cell recognition of CD19 was dependent upon a soluble “switch” molecule, which allowed for the temporal control of CAR T cell activation . Using this model, the authors demonstrated enhanced CAR T cell persistence and re‐expansion when the CAR T cells experience antigen activation in a pulsatile manner as opposed to continuous activation by endogenous CD19 .…”
Section: Antigen Positive Escape and Car T Cell Persistencesupporting
confidence: 53%
“…[66][67][68][69] This hypothesis is further supported by preclinical data in which CAR T cell recognition of CD19 was dependent upon a soluble "switch" molecule, which allowed for the temporal control of CAR T cell activation. 70 Using this model, the authors demonstrated enhanced CAR T cell persistence and re-expansion when the CAR T cells experience antigen activation in a pulsatile manner as opposed to continuous activation by endogenous CD19. 70 These data highlight the potential loss of T cell efficacy and persistence which can occur under conditions of chronic antigen stimulation, much in the way that tonic signaling of CAR molecules negatively impacts CAR T cell efficacy.…”
Section: Rived Cd19-28z Car T Cells In Patients With B-lineage Lymphomentioning
confidence: 99%
See 1 more Smart Citation
“…However, a single distal ITAM increased CAR T cell persistence and the generation of central memory cells. Recently, switchable CAR systems that allow in vivo rest and restimulation cycles, were reported to improve CAR T cell memory . Therefore, signal strength tuning of CAR signaling is critical to balance the outcomes of effector and memory cell development.…”
Section: Strategies To Enhance Car T Cell Persistence and Memorymentioning
confidence: 99%
“…Robust and controllable convertibleCAR-T expansion in patients may supplant the need for lymphodepletion, allowing for retention of endogenous immune functions that are fully competent to support the initial convertibleCAR-mediated anti-tumor activity. Another clinical strategy might be to deliver cytokineligand fusions to bolster convertibleCAR-T function, possibly with a cycling regimen to reduce T cell exhaustion and promote the maintenance of memory T cells 30 . And lastly, as CARs have been demonstrated to persist in humans for years post-infusion 31 , the ability to recall resident convertibleCAR-Ts to attack primary or secondary malignancies (either with the original targeting MicAbody or a different one) without having to re-engineer or generate a new batch of CAR cells should be highly advantageous.…”
Section: Discussionmentioning
confidence: 99%